Identification of quantitative trait loci for yield traits and fine-mapping of qGW4 using the chromosome segment substitution line-Z708 and dissected single-segment substitution lines - Zhou, Kai; Yu, Jinjin; Yu, Zhaopeng; Chi, Chunyu; Ren, Jialin; Zhao, Zhuowen; Zhang, Han; Ling, Yinghua; Zhang, Changwei; Zhao, Fangming (Frontiers in Plant Science, 2025)
Identifying quantitative trait loci (QTL) for yield traits using single-segment substitution lines (SSSL) is essential for both targeted breeding and functional analysis of key genes. Here, a wide-grain rice chromosome segment substitution line (CSSL), Z708, carrying four substitution segments from Jinhui35 in the genetic background of Xihui18, was used to identify the QTL associated with grain size. Seven QTL for yield-related traits (qGW4, qRLW4, qGWT4, qGW5, qRLW5, qGWT5, and qGPP5) were identified on the substitution segments of the fourth and fifth chromosomes of Z708. Subsequently, four SSSLs (S1-S4), which harbored 16 QTL for yield traits, were constructed using molecular marker-assisted selection. These lines (S1-S4) exhibited a significant increase in yield per plant compared to that of Xihui18. Among them, qGW4, which controls wide grains, belongs to a single dominant gene action in S1 based on the frequency distribution of grain width and chi-square test analysis. Finally, qGW4 was fine-mapped to the interval of 80-kb (minimum) and 310-kb (maximum) using both traditional fine mapping and overlapping substitution mapping of the newly constructed secondary SSSLs (S5-S8). Within this interval, four previously unreported candidate genes were predicted.